MINAT PEREMPUAN MINANGKABAU PADA POLITIK MASIH RENDAH - Nurwani - Idris (Wacana Journal of Social and Humanity Studies, 2010)
Abstract Â  In this paper â€œberpolitikâ€ is participation in political domain, to get in parliament to take a part in Governor candidate, Mayor candidate and Kepala Nagari candidate, etc., in affirmative action. Itâ€™s difficult to realize that because so many barriers: political situation, economic, political culture in recruitment system, perforate system in general election, the act of law; government good will to woman candidate; political party attention not yet in affirmative action (external factors). And so on woman participation can be realize with woman political motivation, woman political competence, women political awareness (internal factors) and so importance how the woman interpreted the politics and how far they believe politics and how far they believe woman leadership. Â  Keywords: Minangkabau women; political believing.